OLIY TA’LIM TIZIMIDA TARBIYAVIY JARAYONLARNI BOSHQARUVDA RAHBAR PROFESSIONALIZMINING AYRIM XUSUSIYATLARI HAQIDA - Farhodov, F.B. (SCIENCE and SOCIETY, 2022)
In this country, information is provided on the features of the manager's professionalism in managing processes in medical institutions in the higher education system.
Keywords: leader; higher education; professionalism; education; intelligence; ability